2011
DOI: 10.1371/journal.pone.0025014
|View full text |Cite
|
Sign up to set email alerts
|

No Adverse Effect of Genetically Modified Antifungal Wheat on Decomposition Dynamics and the Soil Fauna Community – A Field Study

Abstract: The cultivation of genetically modified (GM) plants has raised several environmental concerns. One of these concerns regards non-target soil fauna organisms, which play an important role in the decomposition of organic matter and hence are largely exposed to GM plant residues. Soil fauna may be directly affected by transgene products or indirectly by pleiotropic effects such as a modified plant metabolism. Thus, ecosystem services and functioning might be affected negatively. In a litterbag experiment in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…Microbial communities such as bacteria, actinomycetes and fungi and soil invertebrate communities such as Collembola, Opisthophora and Acarina, which were studied in the same cotton fields investigated in the present study, showed no significant differences in abundance and diversity between transgenic insect-resistant cotton and non- Bt cultivars [76], [77]. These findings are consistent with the results of another study examining the effect of transgenic insect-resistant plants on microbial populations [75], [78], [79] and other soil organisms, such as Collembola, mites and earthworms [62], [80][82]. Clearly, soil organisms are not impacted or are only slightly impacted by the cultivation of transgenic insect-resistant cotton.…”
Section: Discussionsupporting
confidence: 92%
“…Microbial communities such as bacteria, actinomycetes and fungi and soil invertebrate communities such as Collembola, Opisthophora and Acarina, which were studied in the same cotton fields investigated in the present study, showed no significant differences in abundance and diversity between transgenic insect-resistant cotton and non- Bt cultivars [76], [77]. These findings are consistent with the results of another study examining the effect of transgenic insect-resistant plants on microbial populations [75], [78], [79] and other soil organisms, such as Collembola, mites and earthworms [62], [80][82]. Clearly, soil organisms are not impacted or are only slightly impacted by the cultivation of transgenic insect-resistant cotton.…”
Section: Discussionsupporting
confidence: 92%
“…In our case, however, the wheat plants carrying Pm3b and Chi and Glu transgenes did not seem to change the post-harvest vegetation, at least within the 6-month time period. Our findings correspond to the results of several companion studies which showed no effects of these particular GM plants on non-target organisms, such as insect species (Alvarez-Alfageme et al, 2011;Peter et al, 2010;von Burg et al, 2010), soil fauna (Duc et al, 2011) or soil beneficial bacteria and mycorrhizal fungi (Meyer et al, 2013;Song Wilson et al, 2010).…”
Section: Post-harvest Weed Vegetationsupporting
confidence: 90%
“…Our study on AMF and pseudomonads revealed similar results as studies on other non-target organisms performed by different groups in the frame of the same field experiments. These studies showed no relevant impact of the pm3b on the abundance of aphids, the cereal leaf beetle Oulema malanopus or the wheat stem fly Chlorops pumilionis [49], on the dipterans Drosophila melanogaster and Megaselia scalaris [50], on the annelid Enchytraeus albidus [51], on aphid-parasitoid food webs [52], [53] and on soil decomposition activity and soil fauna [54].…”
Section: Discussionmentioning
confidence: 95%